FORMULA OPTIMIZATION OF ORALLY DISINTEGRATING TABLET CONTAINING MELOXICAM NANOPARTICLES - Winarti, Lina; Ameliana, Lidya; Nurahmanto, Dwi (Indonesian Journal of Pharmacy, 2017)
Meloxicam is one of oxicams anti-inflamatory drugs that are effective to relieve toothaches, arthritis, dysmenorrhea, and fever. Meloxicam in this study was milled with High Energy Milling (HEM) method to obtain its nano size and then direct compression method was used to produce Orally Disintegrating Tablet (ODT). ODT is designed to be rapidly dissolved on the tongue within a minute. It can be administered without water or chewing and may improve the bioavailability and effectiveness of the drug, and increase the patient’s adherence. The present study aimed to understand the effects of Ac-Di-Sol and Kollidon CL as superdisintegrants, that were used separately or in combination, on the characteristics of nanoparticles meloxicam ODT. It was also to obtain the best proportion of combination between Ac-Di-Sol and Kollidon CL that can produce the optimum formula of meloxicam ODT. The effects of single or combined superdisintegrants were evaluated using Simplex Lattice Design (SLD). Ac-Di-Sol (X1) and Kollidon CL (X2) were the independent variables, while the dependent variables were friability (Y1), disintegrating time (Y2), wetting time (Y3), and percent meloxicam release after 60 seconds (Y4). Optimization of five nanoparticle meloxicam ODT formulas was conducted using Design Expert 7.1.5. The combination of Ac-Di-Sol 4.05mg (X1) and Kollidon CL 10.95mg (X2) in 150mg nanoparticles meloxicam ODT can produce optimal ODT characteristics. After verification there was no difference between predicted value and observed value with p value > 0.05.